2015
DOI: 10.1212/wnl.0000000000001419
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcome after deep brain stimulation for Parkinson disease

Abstract: This study provides Class I evidence that there is no large difference in neuropsychological outcome between GPi DBS and STN DBS after 12 months. The study lacks the precision to exclude a moderate difference in outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 19 publications
5
81
1
5
Order By: Relevance
“…Nevertheless, it is not unusual that the beneficial effect of DBS is mitigated by various side-effects such as dysarthria, decrease in verbal fluency, and changes in behaviour, fatigue, and depression [46]. Careful selection criteria of patients considered for DBS have been established, including Levodopa response, age, normal brain MRI, good cognition, and realistic expectations [3, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is not unusual that the beneficial effect of DBS is mitigated by various side-effects such as dysarthria, decrease in verbal fluency, and changes in behaviour, fatigue, and depression [46]. Careful selection criteria of patients considered for DBS have been established, including Levodopa response, age, normal brain MRI, good cognition, and realistic expectations [3, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the effects on cognitive function, a decline in verbal fluency, response inhibition, and memory has been reported [3,4,5,6]. A long-term follow-up study showed a stepwise decrease in verbal fluency and response inhibition during 10 years after surgery compared to a baseline assessment prior to surgery, whereas verbal memory showed an improvement in the first year after surgery and a decrease from 1 to 10 years after surgery [2].…”
Section: Introductionmentioning
confidence: 99%
“…There is no difference in motor improvement between globus pallidal stimulation and subthalamic stimulation, however, depression deteriorate more in subthalamic stimulation than pallidal stimulation [37]. There is no significant difference in cognition level between subthalamic stimulation and pallidal stimulation [38]. Adverse events of DBS are intraparenchymal haemorrhage, intracerebral infection and decline in verbal fluency [39][40][41].…”
Section: Deep Brain Stimulation (Dbs) Surgerymentioning
confidence: 99%